2008
DOI: 10.1590/s1516-635x2008000100003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of egg pre-storage heating period and storage length on incubation results

Abstract: This experiment aimed at evaluating the influence of different heating times of settable eggs of Cobb 500® broiler breeders before submitting them to different storage periods on egg weight loss, embryo mortality, and hatchability. A total number of 1,980 eggs were distributed in a completely randomized experimental design with a 3 x 3 factorial arrangement, comprising nine treatments with 22 replicates of 10 eggs each. The following factors were analyzed: pre-storage heating periods (0, 6, 12 hours at 36.92°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
20
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 19 publications
(20 reference statements)
7
20
2
1
Order By: Relevance
“…Thus, embryo viability decreases during egg storage due to cell death, even if eggs are stored at a temperature below 20 °C (Bloom et al, 1998). However, in contrast to studies reporting that a longer heat treatment time may also be harmful to chicken embryos (Fasenko et al, 2001b;Silva et al, 2008;Reijrink et al, 2009), positive effects were found in the present study. This may be due to the fact that the breeder flock is young and the storage period is short.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Thus, embryo viability decreases during egg storage due to cell death, even if eggs are stored at a temperature below 20 °C (Bloom et al, 1998). However, in contrast to studies reporting that a longer heat treatment time may also be harmful to chicken embryos (Fasenko et al, 2001b;Silva et al, 2008;Reijrink et al, 2009), positive effects were found in the present study. This may be due to the fact that the breeder flock is young and the storage period is short.…”
Section: Discussioncontrasting
confidence: 90%
“…When the hypoplast stage occurs before storage (Fasenko et al, 2001a;Reijrink et al, 2009), shorter incubation time, higher embryo viability and hatchability are observed. Therefore, pre-storage heating may improve the incubation results (Fasenko et al, 2001a, b;Renema et al, 2006;Silva et al, 2008). During storage, the eggs stop growing, below physiological zero (20-21 °C), at a stage characterized by complete formation of zona pellucid.…”
Section: Introductionmentioning
confidence: 99%
“…RESULTS AND DISCUSSION The current results (Table1) showed that neither the length of pre-incubation storage period nor SPIDES treatment affect the measured of internal or external egg quality traits during storage period. Similar results were observed by Silva et al (2008). They reported that internal and external egg qualities of hatching eggs were not different among three different collection days, hatching eggs were collected in three five-day intervals throughout 14 days.…”
Section: Discussionsupporting
confidence: 84%
“…It was conceivable that a longer egg storage period in experiment 1 could have yielded different results. However, a longer heat treatment period could also be harmful to chicken embryos, as the stage of embryonic development might be further advanced than the optimal stage for prolonged egg storage (Fasenko et al, 2001b;Silva et al, 2008;Reijrink et al, 2009). Nevertheless, a longer heating period has been reported to improve the hatchability of turkey eggs (Fasenko et al, 2001a).…”
Section: Resultsmentioning
confidence: 99%